FRITZ JAHR’S LEGACY AND THE MACEDONIAN BIOETHICS (Annual of the Faculty of Philosophy in Skopje, 2025)
In 1785 Kant only requested that we must “respect every living being in principleas a purpose in itself and, if possible”, (to) “treat it as such!”. While the “Sanctityof the Moral Law” was the basis for Kant’s Categorical Imperative, for Fritz Jahr’sBioethical Imperative, it was “Sanctity of Life”, i.e. compassion with all forms of life andliving together.Having or not, this in mind, this theoretical base for bioethical reflection, in1971 (when the name and practice of bioethics appears in the world), our prof. PavaoVuk-Pavlovic, in his last university lecture, left the students of the Faculty of Philosophyin Skopje the legacy to: “Take care of the living and create loving: Love the life!”.And with this, the seeds for academic investigations and researches about bioethicalsensitiveness and around bioethics were sowed, but not recognized and undeveloped inthat time.From today’s perspective, unlike many neighboring countries on the Balkan, inMacedonia we doesn’t talk about bioethics as a developed discipline or as a part ofscientific activities and research, or even less, bioethics as something that is a systematicpart of education, including bioethical education, up ‘till, at least, the last ten to fifteenyears, and still with enormous difficulties and obstacles. Do we have any kind of tracein term of history of the bioethical discovering efforts in the meanwhile from 1971 orearlier? Even more, what kind of future do we have for the next generations and thesame future generation? What happened in Macedonia with the Jahr’s legacy and hisbioethical imperative?
Keywords: bioethics; bioethical education; Jahr; life; living; scientific activities